2000
DOI: 10.1128/iai.68.4.2231-2236.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of HLA and Age on Levels of Antibody toPlasmodium falciparumRhoptry-Associated Proteins 1 and 2

Abstract: The Plasmodium falciparum rhoptry-associated proteins 1 and 2 (RAP1 and RAP2) are candidate antigens for a subunit malaria vaccine. The design of the study, which looks at the acquisition of immunity to malaria from childhood to old age, has allowed us to document the interaction of HLA and age on levels of antibody to specific malarial antigens. Antibodies reach maximum levels to RAP1 after the age of 15 but to RAP2 only after the age of 30. The effect of HLA-DRB1 and -DQB1 and age on levels of antibody to rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Single-allele analysis of the DQB1 alleles with RAP1 antibody level resulted in confirmation of the previously reported association between RAP1 and DQB1*03 (23). Detailed results are not given since these analyses are not a replication on a new or additional sample but rather a replication on an enriched sample from the same group as the original study.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Single-allele analysis of the DQB1 alleles with RAP1 antibody level resulted in confirmation of the previously reported association between RAP1 and DQB1*03 (23). Detailed results are not given since these analyses are not a replication on a new or additional sample but rather a replication on an enriched sample from the same group as the original study.…”
Section: Resultssupporting
confidence: 57%
“…Results show that, in addition to the previously reported influence of HLA on levels of antibodies to RAP1 and RAP2 (23), HLA class II allelic products influence the level of antibodies to the variant of rAMA1 tested. No HLA influence was observed for the variant of MSA2 and MSP1-190L tested or for any of the MSP1 19 variants used in the study.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Although their contents are only transiently accessible to antibodies, seroepidemiological studies have demonstrated the development of antibody responses to the rhoptry proteins RhopH3, RAP1, and RAP2 following infection (8,12,20,23). In vitro growth inhibition assays have indicated that antibodies directed against the RAP1 and RAP2 proteins have inhibitory effects on P. falciparum growth in in vitro culture (6,9,14,18).…”
mentioning
confidence: 99%